Global collaboration and innovation in malignant cerebral edema research: a bibliometric perspective - Xinhua Peng; Xinhua Peng; Rongrong Zhu; Ke Zhang; Jianghong Ji; Chuanguo Lv; Feng Feng; Feng Feng (Frontiers in Neurology, 2025)
AimMalignant cerebral edema (MCE) is a life-threatening complication of acute brain injuries, with mortality rates exceeding 80% in the absence of treatment. Despite advancements in osmotic therapies and decompressive craniectomy (DC), MCE continues to pose substantial clinical challenges. This study systematically maps the evolution of MCE research (2005–2024) to identify key trends, research gaps, and future priorities.MethodsA bibliometric analysis of 1,460 peer-reviewed articles from the Web of Science Core Collection was conducted using CiteSpace, VOSviewer, and Bibliometrix. Key metrics included publication trends, geographic and institutional contributions, keyword co-occurrence, citation networks, and co-authorship patterns.ResultsAnnual publications increased from 55 in 2005 to 128 in 2024, progressing through three distinct phases: Foundational growth (2005–2009), consolidation (2010–2014), and rapid expansion (2015–2024). The United States (28.9%) and China (18.7%) dominated research output, with Harvard University and the University of California System leading institutional collaboration clusters. High-impact journals highlighted clinical advancements, including Stroke (h-index = 27). Keyword analysis demonstrated a thematic progression from blood–brain barrier pathophysiology to clinical innovations, including DC and emerging predictive modeling techniques incorporating machine learning. Landmark trials, including DECIMAL and HAMLET, validated early surgical intervention, while emerging trends have emphasized precision medicine and artificial intelligence (AI)-driven risk stratification.ConclusionThe MCE research has transitioned from foundational pathophysiology to interdisciplinary clinical practice and data integration. However, critical gaps remain, including underrepresentation in pediatric research, disparities in global neurocritical care, and challenges in translational application. Future priorities should focus on biomarker discovery, equitable global collaborations, and AI-enhanced frameworks to transform survival into functional recovery worldwide.